2012
DOI: 10.1002/pip.2217
|View full text |Cite
|
Sign up to set email alerts
|

Improved conductive atomic force microscopy measurements on organic photovoltaic materials via mitigation of contact area uncertainty

Abstract: Physical processes that lead to conversion of light into electrical energy inside photovoltaic devices happen at the nanoscale. Therefore, understanding of electrical properties of photovoltaic materials at this length scale is of paramount importance for improvement of device performance. In this paper, we describe and validate a new framework for high‐resolution quantitative measurements of electrical and mechanical properties of compliant materials with sub‐100‐nm resolution. Previous approaches have genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
(45 reference statements)
0
16
1
Order By: Relevance
“…This temperature is below the glass transition temperature and the melting temperature of PCDTBT ( T g ≈ 130 °C and T m ≈ 200 °C) and its of PC 71 BM ( T g ≈ 130 °C T m ≈ 319 °C), therefore a layer of closely packed particles with a high roughness of 30 nm is formed after spray‐coating (Figure a). However, conducting AFM showed that the film appears homogeneous from a charge conduction point of view (Figure b), in the limits of the uncertainty introduced in the measurement due to the varying contact area between the AFM tip and the surface of the film . This observation implies that the donor and the acceptor not only coexist within the composite particles but also they are very well mixed, forming a single donor:acceptor phase.…”
Section: Resultsmentioning
confidence: 97%
“…This temperature is below the glass transition temperature and the melting temperature of PCDTBT ( T g ≈ 130 °C and T m ≈ 200 °C) and its of PC 71 BM ( T g ≈ 130 °C T m ≈ 319 °C), therefore a layer of closely packed particles with a high roughness of 30 nm is formed after spray‐coating (Figure a). However, conducting AFM showed that the film appears homogeneous from a charge conduction point of view (Figure b), in the limits of the uncertainty introduced in the measurement due to the varying contact area between the AFM tip and the surface of the film . This observation implies that the donor and the acceptor not only coexist within the composite particles but also they are very well mixed, forming a single donor:acceptor phase.…”
Section: Resultsmentioning
confidence: 97%
“…Although the mechanical properties of the active layer is important for practical applications of PSCs, information related to these properties is scarcely reported 31. 32 In this work, the mechanical properties of PBDTTT‐C‐T:PC 70 BM and PBDTTT‐C‐T:PC 70 BM:G–CdS (1.5 wt %) are examined by Young’s modulus and adhesion measurements (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…32 In this work, the mechanical properties of PBDTTT‐C‐T:PC 70 BM and PBDTTT‐C‐T:PC 70 BM:G–CdS (1.5 wt %) are examined by Young’s modulus and adhesion measurements (Figure 9). Young’s modulus measurements provide information about the mechanical properties of the sample within several tens of nanometers from the surface (penetration depth is determined by the propagation of strain induced by AFM probe indentation) and allow inference about the composition of the surface layer 31. Adhesion influences the degree of deformation of the roughness of the structures at the contact.…”
Section: Resultsmentioning
confidence: 99%
“…AFM is a very common and useful technique that investigates the surface information of the sample at the micrometer and nanometer scales with high spatial resolution within 10 nm. [36] Its operating principle is that the probe contacts the sample surface, through the van der Waals interaction between them and the feedback mechanism, the sample surface information (such as height, phase distribution, modulus [66,129,130] of the sample) can be obtained. Among these, height and phase images in AFM are often used to describe the morphology of thin films.…”
Section: Characterization Tools Of Aggregated Structuresmentioning
confidence: 99%